Peran TPA dalam Membentuk Karakter Islami Anak melalui Kegiatan Mengaji dan Pembinaan Akhlak di Desa Kertonatan: The Role of TAP in Shaping Children's Islamic Character through Koran Recitation Activities and Moral Development in Kertonatan Village - Risma Ratna Safira; Nashwa Callista Mahardika; Asa Sulistyaningsih; Nabila Arsida; Intan Apriliyanti; Vika Rosalia Agustin; Aprilia Rahma Yunan Sari Romodar; Juvita Daniati; Ahmad Nurrohim (Litera Academica Publishing, 2025)
The main activity in this community service aims to strengthen the role of TPA in developing children's Islamic character through three main activities carried out, namely strengthening YPA activities, learning to read and write the Koran and introducing good interpretation of the Koran. Taking place in Kertonan village, Kartasura subdistrict, this activity was motivated by the limited number of TPA teachers, the weak ability to read and write the Koran and Iqro among children and the lack of in-depth understanding of the meaning of the holy verses of the Koran. In carrying out this service activity, we invite children not only to read fluently but also to understand the meaning and moral values ​​of the verses and prayers that children often learn in everyday life. With this activity, children show an increase in their ability to read Iqro and the Koran, and begin to get used to practicing Islamic teachings in their daily lives. For community activities, reciting the interpretation of the Koran is also very helpful in increasing people's knowledge in understanding Islamic religious knowledge. The results of this activity show that the strategy used is very efficient in teaching Islamic religion through TPA activities, able to strengthen the foundation of Islamic character from an early age and can foster a strong religious spirit in children in the Kertonan village.